2020
DOI: 10.1038/s41598-020-68865-8
|View full text |Cite
|
Sign up to set email alerts
|

Facile formulation and fabrication of the cathode using a self-lithiated carbon for all-solid-state batteries

Abstract: We propose a innovative concept to boost the electrochemical performance of cathode composite electrodes using surface-modified carbons with hydrophilic moieties to increase their dispersion in a Lithium nickel Manganese cobalt oxide (nMc) cathode and in-situ generate Li-rich carbon surfaces. Using a rapid aqueous process, the hydrophilic carbon is effectively dispersed in NMC particles followed by the conversion of its acid surface groups (e.g.-COOH), which interact with the NMC particles due to their basicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The components contained in the sample are also confirmed using Energy Dispersive X-ray (EDX), which is presented in table 1. Based on the EDX results, there are impurities in the samples, so it is necessary to do a post-treatment such as re-washing and re-heated to remove the Na content in the sample [16], [17].…”
Section: Resultsmentioning
confidence: 99%
“…The components contained in the sample are also confirmed using Energy Dispersive X-ray (EDX), which is presented in table 1. Based on the EDX results, there are impurities in the samples, so it is necessary to do a post-treatment such as re-washing and re-heated to remove the Na content in the sample [16], [17].…”
Section: Resultsmentioning
confidence: 99%
“…Among these, the last three evidences are more likely to support the mechanism of the proton-cation exchange theory. [34,35] Recently, Hartmann et al used TGA-MS to study the formation rate of surface contaminants of NCM851005 during wet storage, reporting that the observed mass loss was accompanied by the onset of H 2 O evolution at ≈160 °C and that of CO 2 evolution at ≈625 °C. Such mass loss is much greater in the samples exposed to humid air than in the pristine samples, and a significant increase occurs as storage time grows, which further confirms the Li + /H + exchange theory during ambient storage of Ni-rich CAMs.…”
Section: Exchange Of Lithium Ion and Protonmentioning
confidence: 99%
“…[16] For Ni-rich CAMs stored in air, early studies have found that it is not enough for the impurities generated by the reaction of residual lithium on the surface with air to explain the significant decline in battery performance, thus reporting that the top layer may consist of adsorbed hydroxyl, bicarbonate, carbonate, and crystalline Li 2 CO 3 . [35] Liu et al used SEM to observe LiNi 0.8 Co 0.2 O 2 for a long time and found that the transparent substance on the surface of the sample would partly disappear over time after storage. For this reason, they put forward the idea that there are adsorbed substances on the surface.…”
Section: Impurities Formed On the Surfacementioning
confidence: 99%
See 1 more Smart Citation